Chemical and Biological Changes Under Force Degradation and Acceleration Condition of the Combination of Ha-Rak Remedy, Piper betle, and Garcinia mangostana Extracts for Atopic Dermatitis - Ubonwan Saesiw; Srisopa Ruangnoo; Arunporn Itharat; Pattama Sriumpai (Hindawi Limited, 2024)
Herbal medicine could be an option for atopic dermatitis (AD) treatment for those suffering from global public health. HMB is a new combination of three herb extracts, consisting of the Ha-Rak (HR) remedy extract, Piper betle (PB) extract, and Garcinia mangostana (GM) extract in equal proportions, using Thai traditional medicine theory, that uses a combination of medications that can improve therapeutic efficacy and reduce side effects and toxicity. HMB extract has anti-inflammatory and antiallergic properties, is a component for AD treatment, and tends to develop topical products. Drug registration requires stability data. Results from drug stability testing affect not only the efficacy of the drug but also its safety. The aim of this study was to investigate stability through forced degradation and an accelerated study of extracts. Chemical content analysis and in vitro biological activities such as anti-inflammatory and antiallergic activities determined the effects of all examined samples. Anti-inflammatory and antiallergic effects were assessed by inhibiting nitric oxide synthesis in RAW 264.7 cells and β-hexosaminidase release in RBL-2H3 cells, respectively. High-performance liquid chromatography (HPLC) assessed content indicators. Moisture and temperature hydrolysis had no significant differences in the chemical or biological properties of the HMB. However, the HMB demonstrated sensitivity to alkaline hydrolysis, showed low anti-inflammatory activity, and decreased hydroxychavicol, eugenol, and α-mangostin contents. The contents of the three compounds also decrease with acid hydrolysis. For the accelerated study, anti-inflammatory and antiallergic effects and hydroxychavicol amount were not significantly different after 180 days at 40°C and 75% RH. Therefore, the contents of eugenol and α-mangostin were changed. Eugenol in HMB decreased significantly from the 15th day until the 180th day of storage. In addition, α-mangostin amounts in HMB decreased slightly on 180th day. Fortunately, reducing the two chemicals did not affect anti-inflammatory or antiallergic effects. For stability, combination extract should be stored in a closed container in the refrigerator at a low temperature and protected from light, high temperature, oxygen, and pH. Further HMB development should avoid pH or oxidation processes or components.